Sustainable Developmental Goals (SDGs) and Eye Health Care in Nepal - Khandekar, Rajiv (Nepalese Journal of Ophthalmology, 2018)
In 2015, the United Nations (UN) adopted the resolution of transforming our world by the year 2030 through the agenda of Sustainable Development with a primary focus on strengthening universal peace with larger freedom [United Nations 2015, Griggs D 2012]. All member countries including Nepal agreed to this ambitious plan for relieving poverty and reducing global inequality over a span of 15 years starting from 2016 to 2030. All the health programs including, Millennium Developmental Goals, universal eye health or Vision 2020 – the elimination of avoidable blindness by 2020 are expected to thrive under the umbrella of Sustainable Development Goals (SDGs). There are 17 goals and 169 targets. The three dimensions of sustainable development - economical, social and environmental - are balanced in this new initiative [eye health Australia 2015]. The overall effect of this initiative will be beneficial to human beings and our planet with human health as one facet among many. All efforts would be directed to review, realign and integrate the ongoing public health activities to attain SGDs [World Health Organization 2016]